PERBANDINGAN PREPARASI KULIT MENGGUNAKAN ALKOHOL-KLORHEKSIDIN DENGAN ALKOHOL-POVIDON IODIN TERHADAP INFEKSI LUKA OPERASI SEKSIO SESAREA - Fahmi, Moh. Nailul; Hadiati, Diah Rumekti; Widad, Shofwal (JURNAL KESEHATAN REPRODUKSI, 2017)
Background: Surgical site infection (SSI) is the second most frequent nosocomial infection and has high morbidity and mortality rate. The use of preoperative skin antiseptics effective in preventing of surgical site infection. There are lack of evidences to evaluate types, concentration and application methods of antiseptic for skin preparation for preventing infection following caesarean sectionObjective: to determine the difference of SSI rate in patients receiving alcohol-chlorhexidine and alcoholpovidone iodine as an agent for skin preparation during caesarean section. Method: The study design was randomized clinical trial. The study was conducted in Dr Sardjito hospital and two affiliated hospital (Saras Husada Hospital and Panembahan Senopati Hospital). Total 174 subjects meeting in inclusion and exclusion criteria were divided into two groups. Experimental group (87 subjects) received alcohol-chlorhexidine as skin preparation antiseptic during caesarean section. Control group (87 subjects) received alcohol-povidone iodine. A computer generated random number was created to assigned subject into experimental and control goups. Outcome assessment was performed on day 3 and day 7 after caesarean section. Surgical site infection was diagnosed based on Center for Disease Control and Prevention (CDC) criteria.Result and Discussion: There were no differences in terms of age, weeks of gestation, body mass index, parity, emergency/elective, duration of operation, duration of membrane rupture, and number of vaginal examination between two groups (P>0.05). SSI rates on day 3 were similar between two groups, alcoholchlorhexidine group was 13.8% (12 subjects) and alcohol-povidone iodine group was 11.5% (10 subjects). Cumulative SSI for 7 days were similar (p=1) between two group, alcohol-chlorhexidine group was 13.8% (12 subjects) and alcohol-povidone iodine group was 12.6% (11 subjects). Conclusions: there were no differences of SSI rates in patients receiving alcohol-chlorhexidine and alcoholpovidone iodine as an agent for skin preparation during caesarean section.Keywords: Surgical site infections, skin preparation, alcohol, povidone iodine, chlorhexidine, caesarean section.